The Effectiveness of the Project-Based Learning Model on Motivation and Learning Outcomes in History Subjects - Ria Alifah; Waris Waris; Fauzan Adhim (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
The purpose of this study is to examine the effectiveness of Canva-based Project-Based Learning (PjBL) in improving students’ learning outcomes and motivation in history education. This quasi-experimental study involved 150 tenth-grade students, with samples selected using cluster random sampling due to class homogeneity. Class X1, consisting of 30 students, was assigned as the experimental group using Canva-based PjBL, while Class X2, with 31 students, was designated as the control group using conventional learning methods. Research instruments included pre-tests and post-tests to assess learning outcomes and questionnaires, and observation sheets to measure motivation. Data were analyzed using normality tests, homogeneity tests, descriptive statistics, and N-Gain tests. The results showed that the experimental group experienced a significant improvement in both learning outcomes and motivation. The experimental class achieved a higher post-test mean score (M = 17.50, SD = 1.43) than the control class (M = 14.52, SD = 2.22), with p < 0.001. The N-Gain value for learning outcomes was 0.7604, and learning motivation was 0.8157, indicating high improvement. These results demonstrate that Canva-based PjBL effectively enhances students’ academic achievement and learning motivation in history classrooms.